A Self‐Repairing Cathode Material for Lithium–Selenium Batteries: Se−C Chemically Bonded Selenium–Graphene Composite. Issue 9 (17th January 2018) - Sha, Linna; Gao, Peng; Ren, Xiaochen; Chi, Qianqian; Chen, Yujin; Yang, Piaoping
Abstract: Lithium–selenium batteries, employing selenium as a cathode material, exhibit some notable advantages, such as high discharge rates and good cycling performance, due to their high electrical conductivity, high output voltages, and high volumetric capacity density. However, an important problem, termed the "shuttle effect", can lead to capacity decay in Li‐Se cells (and in Li‐S cells), which arises from aggregation and the loss of Se or S from the cathode into the electrolyte. In this work, in order to solve this problem, a new self‐repairing system has been devised, in which some Se atoms are chemically bonded to the carbon atoms of graphene and act as reclaiming points for dissociated Se atoms through the establishment of ‐Se‐Se‐Se‐ chains. Se‐decorated graphene (Se‐GE) was first constructed through a facile high‐energy ball‐milling process. Its formation was confirmed by XRD, SEM, HRTEM, XPS, and Raman analyses. As we anticipated, in examining cell properties, the as‐prepared Se‐GE composite underwent an initial capacity decay in the first 20 cycles (from 1050 mAh g −1 to 750 mAh g −1, ca. 29 % loss), but the capacity then reverted to 970 mAh g −1 (ca. 92 % of the initial value). Other measurements were also consistent with the recapture of dissociated Se atoms. Abstract : Let it Se : An Se−C‐bonded interface has been constructed in a Se–graphene (GE) composite through facile high‐energy ball‐milling. Due to the presence of Se−C bonds, a new self‐repairing Se‐GE cathode material has been obtained (see graphic). It shows high reversible capacity, long cycle life, and high coulombic efficiency.